2023
DOI: 10.19126/suje.1268001
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Dersi̇nde Alternati̇f Bi̇r Model Kullanmak: Harezmi̇ Eği̇ti̇m Modeli̇

Ahmet TOKMAK,
Ali YILMAZ,
Mustafa ŞEKER

Abstract: The Harezmi education model is a teaching model that was designed to equip students with various types of skills about various subjects or problem situations in an interdisciplinary manner. The research examined the students’ views and the effects of using the Harezmi Education Model for teaching the social studies course on the students in terms of academic achievement, permanent learning, meta-cognitive awareness. The research was carried out using the diversification of (parallel-convergent design) mixed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…Although there are no studies on science lesson in the literature, studies indicate that they improve student achievement in social studies courses (Tokmak, 2022). Tokmak et al (2022) found a significant difference in their students' algorithm subdimension scores because of their study titled "the effect of the HEM on the cognitive thinking skills of secondary school students."…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are no studies on science lesson in the literature, studies indicate that they improve student achievement in social studies courses (Tokmak, 2022). Tokmak et al (2022) found a significant difference in their students' algorithm subdimension scores because of their study titled "the effect of the HEM on the cognitive thinking skills of secondary school students."…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…In the study Arslan-Namli and Aybek (2022) conducted with 5thgrade students in the context of the effect of block-based programming, the achievement of computational thinking skills, self-efficacy, and computer science teaching activities without computers in academic subjects is similar to this study in which HEM designed science teaching was carried out. Tokmak et al (2023), in their research titled using an alternative model in the social studies course: Harezmi Education Model, found that the HEM used in teaching the social studies course had a significant and positive effect on the academic achievement of 7th-grade students. In their research, Yavuz et al (2019b) found that students' creativity scores increased within the scope of the HEM.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beş temel zemin ya da kök üzerine dizayn edilen HEM; bir konuya ilişkin problem çözme süreçlerinde bilgi işlemsel düşünme becerilerinin kullanılması, öğretim ortamı ve süreçlerinde programlama araçlarının kullanılması, problem çözme süreçlerinde disiplinlerarası yaklaşım dikkate alınarak farklı disiplin alanlarının ortak olarak hareket etmesi, robotik ve oyun tasarımı ile bireysel yapılandırma ve anlamlı öğrenmenin sağlanması, diğer bilimler ile sosyal bilimlerin bir araya getirilerek bütünleştirilmesi süreçlerini içerisinde barındıran bir eğitim modelidir. Modele Ebû Ca'fer Muhammed bin Mûsâ el-Hârizmî'nin isminin verilmesinde ise; Harezmi'nin sistematik, disiplinlerarası düşünme şekli, algoritmik düşünme yapısı ve modelin öğrencilere kazandırmaya çalıştığı beceriler ile Harezmi'nin bu bağlamda benzeşen özelliklerinin etkili olduğu söylenebilir (Koçoğlu, 2018;Seçer, 2021;Tokmak, Yılmaz & Şeker, 2023).…”
Section: Introductionunclassified